Menthol-Camphor-Thymol-Eucalyptus Compound as a Novel Adjuvant Therapy in Fluconazole-Treated Candida parapsilosis Onychomycosis: A Case Report - Nurrachmat Mulianto; Nurul Hidayati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Onychomycosis, a fungal infection of the nail apparatus, presents a therapeutic challenge due to its recalcitrant nature and the limitations of current antifungal regimens, including potential side effects and prolonged treatment durations. Candida parapsilosis is an increasingly recognized, yet less commonly reported, yeast pathogen in onychomycosis, particularly in immunocompromised individuals or those with specific comorbidities. The exploration of effective, safe, and accessible adjuvant therapies is crucial to enhance treatment outcomes. This report details the use of an over-the-counter menthol-camphor-thymol-eucalyptus compound as an adjuvant to oral fluconazole. Case presentation: A 69-year-old male, a gold washer by occupation with a two-month history of rheumatoid arthritis (RA) treated with methotrexate, hydroxychloroquine, methylprednisolone, and celecoxib, presented with a four-month history of yellowish-brown discoloration, uneven texture, and brittleness of both thumb nails. Dermatological examination revealed onychodystrophy, subungual hyperkeratosis, and yellowish-brown discoloration of the bilateral thumb nail plates. Dermoscopy confirmed these findings. Fungal culture of nail clippings identified Candida parapsilosis. The patient was treated with oral fluconazole 150 mg weekly for three months and twice-daily topical application of menthol-camphor-thymol-eucalyptus compound under plastic occlusion. Significant clinical improvement in nail color and texture, with no onycholysis, was observed at the 6-week follow-up. At the 3-month evaluation, fungal culture was negative, and liver function tests remained within normal limits. Conclusion: This case demonstrates the successful use of a menthol-camphor-thymol-eucalyptus compound as an adjuvant to oral fluconazole in treating Candida parapsilosis onychomycosis in an elderly patient with RA. The combination therapy was well-tolerated and led to clinical and mycological resolution, suggesting a promising, accessible, and cost-effective adjunctive therapeutic strategy.